'Scènes de Gynécées' : figured Ostraca from New Kingdom Egypt : iconography and intent - Backhouse, Joanne (Archaeopress Egyptology, 2020)
This work examines images of women and children drawn on ostraca from Deir el-Medina, referred to in previous scholarship as 'Scènes de Gynécées'. This publication represents the first systematic study of this material, and it brings together ostraca from museums worldwide to form a corpus united contextually, thematically and stylistically.